CONCEPTUAL APPROACHES FOR DETERMINATION OF PRODUCTION AND TECHNOLOGICAL POTENTIAL IN TRAFFIC ROLLING STOCK PROJECTS (Transport systems and technologies, 2022)
The article considers the problems of managing the efficiency of use of production and technological potential of rolling stock. It is investigated that in order to improve the efficiency of functioning it is necessary to determine the conceptual approaches of the components of the processes of maintenance and operation of rolling stock. This requires the use of technical means and methods of monitoring the technical condition of the wheelsets of the rolling stock. It is investigated that the possibility of successful solution of one of the important tasks of the railway industry risk of improving the quality of repair and restoration works and prolonging the life cycle of rolling stock is possible by ensuring control over finished products and improving process management.It is determined that the form of the concept of conceptual approaches to determining the essence of production and technological potential of maintenance and operation of traction rolling stock is a model of the life cycle of maintenance and development of its operation. A detailed analysis of the advantages and disadvantages of existing methods of quality control of repair of wheelsets of railway rolling stock. Ways to increase the life cycle of wheelsets are considered. The mathematical model of a complex estimation of quality of repair of wheel pairs that will increase efficiency of operational work of a rolling stock and safety of transport process is offered.The paper considers the components of conceptual approaches to improving the functioning of production and technological potential of the transport complex in the projects of traction rolling stock.
Keywords: traction rolling stock, model, diagnostic methods, technical means. production potential, information technology.